2023
DOI: 10.3390/su15021378
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Scheduling of Home Energy Management Controller (HEMC) Using Heuristic Optimization Techniques

Abstract: The main problem for both the utility companies and the end-used is to efficiently schedule the home appliances using energy management to optimize energy consumption. The microgrid, macro grid, and Smart Grid (SG) are state-of-the-art technology that is user and environment-friendly, reliable, flexible, and controllable. Both utility companies and end-users are interested in effectively utilizing different heuristic optimization techniques to address demand-supply management efficiently based on consumption p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Step (1) The first step of the fuzzy hierarchical analysis process method, such as the deterministic AHP method, is drawing the hierarchical structure or hierarchical state of the research problem. It should be noted that this issue has only two levels of goals and main indicators.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Step (1) The first step of the fuzzy hierarchical analysis process method, such as the deterministic AHP method, is drawing the hierarchical structure or hierarchical state of the research problem. It should be noted that this issue has only two levels of goals and main indicators.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the increase in waste production and the concerns related to the resulting ecological damage [1], waste management policy has become extremely important [2]. Waste is a by-product of human activities in urban areas, and residential homes are one of these areas [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Needed more accuracy. [30] The authors suggested employing heuristic optimization techniques to schedule the Home Energy Management Controller (HEMC) effectively.…”
Section: References Groups Reference Contributions Shortcomingsmentioning
confidence: 99%